Energi Terbarukan untuk Pertanian Modern: Studi Kasus pada Budidaya Hidroponik UMKM Rumah Bali Hidroponik: Renewable Energy for Modern Agriculture: A Case Study on Hydroponic Cultivation at Rumah Bali Hydroponic SME - Herdhiansyah, Dhian; Asriani, Asriani; Aksara, L. M. Fid; L, Mariani (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Renewable energy, particularly Solar Power Plants (PLTS), holds significant potential to enhance sustainability and efficiency in modern agriculture, including for small and medium-sized enterprises (SMEs) utilizing hydroponic technology. This Community Partnership Program (PKM) aims to implement a PLTS system to improve the productivity and sustainability of hydroponic cultivation at Rumah Bali Hydroponic SME. The methods employed include installing a PLTS system to meet energy demands in hydroponic farming processes and providing technical training for SME partners on managing and utilizing solar energy. Evaluations were conducted to measure energy efficiency, impacts on plant productivity, and contributions to reducing operational costs. The results demonstrated that the PLTS system reduced dependency on conventional energy sources, decreased operational costs by 15%, and increased hydroponic crop productivity by 18%. Additionally, training sessions significantly enhanced participants' understanding of solar energy technology, with a 90% improvement in technical comprehension. The positive impact on carbon emission reduction further supports environmentally friendly agriculture. In conclusion, applying PLTS in hydroponic farming at Rumah Bali Hydroponic SME improved energy efficiency, productivity, and business sustainability. This program provides economic benefits and promotes sustainable agriculture, serving as a model for empowerment initiatives applicable to Indonesia's agricultural sector.